An examination of the teacher’s questions for revealing students’ mathematical thinking [Öğrencilerin matematiksel düşüncelerini ortaya çıkarmaya yönelik öğretmen sorularının İncelenmesi] - Bozkurt, A.; Polat, S. (Karadeniz Technical University, 2018)
This study examines sixth grade students’ mathematical thinking through comparing their teacher's questions and their answers to these questions. Five class videos taken consecutively in a particular sixth-grade classroom taught by a mathematics teacher were used as data resource. The dialogues in the videos were transcribed. The data were qualitatively analyzed. Within the scope of the analysis, codes were formed out of the participants’ answers, and their frequencies were calculated. According to the results, the teacher often used specific questions to remove students' missing, incorrect or uncertain answers, while they rarely used leading question types. Also, he used general questions to allow the students to elaborate their explanations, thereby encouraging them to rethink their answers. Moreover, when the students answers were accurate and sufficient, the teacher preferred general question types. © Karadeniz Technical University. All rights reserved.
Keywords: Mathematical thinking; Student’s answers; Teacher’s questions; Type of questions